Pengembangan Paket Pembelajaran IPA Terpadu Kelas VIII SMPN 2 Cimanggu Kecamatan Cimanggu Kabupaten Pandeglang Untuk Meningkatkan Hasil Belajar IPA - Devi Elisa; Suyitno Muslim; Etin Solihatin (Peneliti.net, 2019)
This study aims to produce a product in the form of an integrated science learning package for students class VIII in junior high school to improve science learning outcomes. research methodology using the R & D method. The development model used is the Derex Rowntree and the design of the Sitepu learning material which consists of three stages; the preparation stage, the writing preparation stage, and the writing and editing stage. The product testing phase begins with the validation of several experts such as material experts, media experts and instructional design experts. With the acquisition of an average material expert of 3.31 media experts with the average of 3.6 and an instructional design expert with the average of 3.85, it means that the integrated science learning package is feasible to use. Furthermore, the product was tested for the number of students of class VIII with one to one test as many as 3 students, obtained an overall average score of 3.36 and the test filed test as many as 22 respondents with an average gain of 3.67. In conclusion, the integrated science learning package developed has been very good and feasible to be used in the science learning process.